(untitled) (Journal of Human Sciences, 2025)
In this study, we are interested in examining the horse poems organized by the Omani poet Mohamed bin Isa bin Saleh al-Harthi, also known as Abu al-Fadl. Our interest in this topic is motivated by the scarcity of studies that focus on the description of horses by this poet and other Omani poets who stood out in this regard. Since Abul Fadl was a horseman of his time and the leader of the cavalry in the Eastern Province of Oman, we devoted the first section to clarifying the status of the horse in the poet’s life before examining it in his poetry, especially in the poems that he called “Khilayat”. We found out that horses are a part of Abul Fadl’s consciousness and that he grew up in an environment where horses and horses are related to each other. We then turned to the poetic code and divided it into two axes: One to consider the characteristics of the discourse in which the horse is one of the meanings of the poem, and the other to consider the poems in which the discourse is limited to the horse and does not go beyond it to other meanings. In a structural approach, we read poetic examples, most of which are from the “Khilayat” poems. In conclusion we note that Al-Harthi was a horseman poet who followed in the footsteps of those famous for describing horses, echoing what was established in the traditional poetic blog about the status and image of horses. On the other hand, in other poems, he introduces some things that the first ones did not. For example, in addition to mentioning them as complainers, boasting, praising, praising, heirs, sufferers, and cynics, he has a long conversation with them and speaks in words that other poets did not use. In addition to describing her in the arena of competitions and in the wilderness, some poets were inspired to say that she was a horse that sprang from no example and was equated to no other, and that he was a commanding knight who could not be outdone.